2021
DOI: 10.3390/ijms222212480
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Bempedoic Acid: Different Actions of Cholesterol Inhibitors on Macrophage Activation

Abstract: Statins represent the most prescribed class of drugs for the treatment of hypercholesterolemia. Effects that go beyond lipid-lowering actions have been suggested to contribute to their beneficial pharmacological properties. Whether and how statins act on macrophages has been a matter of debate. In the present study, we aimed at characterizing the impact of statins on macrophage polarization and comparing these to the effects of bempedoic acid, a recently registered drug for the treatment of hypercholesterolemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 82 publications
(123 reference statements)
1
15
0
Order By: Relevance
“…Moreover, in agreement with anti-inflammatory reports, they noted a decreased surface expression of MHC-II. Another study by Linnenberger et al agreed with this finding that statin treatment had no effect on macrophage stimulation by IFN-γ (despite enhancing LPS-induced expression of TNF, IL-1β, and IL-6) [97].…”
Section: Pro-inflammatory Modulation Of Ifn-γr Signalling Pathwaysmentioning
confidence: 64%
See 2 more Smart Citations
“…Moreover, in agreement with anti-inflammatory reports, they noted a decreased surface expression of MHC-II. Another study by Linnenberger et al agreed with this finding that statin treatment had no effect on macrophage stimulation by IFN-γ (despite enhancing LPS-induced expression of TNF, IL-1β, and IL-6) [97].…”
Section: Pro-inflammatory Modulation Of Ifn-γr Signalling Pathwaysmentioning
confidence: 64%
“…Specifically, statin treatment decreased c-FOS binding to the AP-1 promoter region (a negative regulator of the signalling system) whilst simultaneously enhancing JNK-mediated c-Jun phosphorylation, thereby stimulating the transcription of inflammatory genes. In keeping with this, atorvastatin and simvastatin pre-treatment is observed to enhance TLR2/TLR4 ligand-stimulated IL-6 and TNFα production [82], and various research groups have found statins to induce the activation of the MyD88 pathway transcription factor NF-κB [92,97]…”
Section: Pro-inflammatory Modulation Of Tlr Signalling Pathwaysmentioning
confidence: 82%
See 1 more Smart Citation
“…BMMs were obtained from wildtype or Nlrp3 knockout C57B/6 mice and cultivated as described previously ( 27 ). Cells were seeded per well into 96 well plates (75,000 per well) for MTT assays and into 12 well plates (500,000 per well) for RT-qPCR.…”
Section: Methodsmentioning
confidence: 99%
“…The paper of Linnenberger and colleagues compared the pro-and anti-inflammatory effects of statins with bempedoic acid (BA), recently registered as a drug for the treatment of hypercholesterolemia. They concluded that BA is effective in the rescue of the phagocytic activity of macrophages differently from statins, and does not induce side effects as statins do [10] (Figure 2F). Modulation of macrophage phenotypes has been suggested as a novel strategy for the treatment of inflammatory pathologies.…”
mentioning
confidence: 97%